2002
DOI: 10.1002/zoo.10040
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of delayed reproductive success in a pair of white‐cheeked gibbons (Hylobates leucogenys)

Abstract: Concern over a lack of breeding success in a pair of white-cheeked gibbons (Hylobates leucogenys) prompted a four-part study of gibbon behavior and physiology at the Lincoln Park Zoo. Data were collected to determine the female intermenstrual interval (IMI) and identify periods of peak receptivity. Subsequent behavioral data were gathered during both female menses and estrous periods to formulate a behavioral profile for each gibbon. The female experienced a speciestypical IMI of 21.6 days and exhibited height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…In addition, whereas other research has suggested differences in solitary behaviors, such as increased activity (Lukas et al, 2002) or autogrooming (Wells, 2005), this research disclosed no differences in solitary behavior patterns.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In addition, whereas other research has suggested differences in solitary behaviors, such as increased activity (Lukas et al, 2002) or autogrooming (Wells, 2005), this research disclosed no differences in solitary behavior patterns.…”
Section: Discussioncontrasting
confidence: 58%
“…Kuhar (2008) reported an increase in aggression in a group of young adult male gorillas, but not in a family group, when exposed to large crowds and proposed that certain age-sex classes may be more likely to react to zoo visitors. Lukas et al (2002) reported differences in activity levels and autogrooming in a pair of white-cheeked gibbons. Vrancken, Van Elsacker, and Verheyen (1990) found a single female gorilla sat close to a glass viewing window when visitors were present but found no changes in behavior from the other four group members.…”
Section: Figurementioning
confidence: 96%
“…Another conceivable explanation is females' importance in shaping the mating system in this species. Among gibbons, copulations initiated by females have been reported in captive western black crested gibbons (Zheng 1988), hoolock gibbons [Hoolock leuconedys (Groves, 1967)] (Yang 1998), white-cheeked gibbons [Nomascus leucogenys (Ogilby, 1840)] (Lukas et al 2002), free-ranging Hainan gibbons (Zhou et al 2008) and Hoolock gibbons (Huang et al 2010). Most observed EPCs have been initiated by males (Palombit 1994;Reichard 1995), although in some cases females have been involved in the initiation (Palombit 1994).…”
Section: Complex Mating Systemmentioning
confidence: 99%
“…Zoo visitor effects on behaviour which have been interpreted as possibly enriching have usually involved feeding by the public, even in circumstances where this was not permitted by the zoo (Cook andHosey, 1995, Fa, 1989). However, although there are reports of individual animals, such as parrots (Nimon and Dalziell, 1992), gorillas (Vrancken et al, 1990) and gibbons (Lukas et al, 2002), who actively solicited contact with the public, there appear to be no empirical studies, other than that of Anderson et al (2002), of whether contact with zoo visitors in itself could be enriching for captive terrestrial mammals.…”
mentioning
confidence: 99%